EFFECTIVENESS OF TELENURSING PROGRAM ON MEDICATION ADHERENCE IN PULMONARY TUBERCULOSIS PATIENTS UNDERGOING OUTPATIENT TREATMENT AT PIDIE DISTRICT HOSPITAL - Mahdani Mahdani; Susi Andriani (Jurnal Keperawatan Respati Yogyakarta, 2023)
Pulmonary tuberculosis is a chronic disease that requires long-term treatment. One of the factors that support healing is adherence to taking medication in patients. Telemedicine is an alternative for providing health and nursing services. nursing is one of the latest information and communication technology systems in the health sector. One form of telemedicine is telenursing. This study aims to determine the degree of medication adherence in pulmonary tuberculosis patients before and after telenursing interventions. This is a quasi-experimental design using a Control Group Design. The sample as a respondent was 200 respondents, using purposive sampling. Data analysis was performed using descriptive statistics and inferential statistics. Medication adherence was measured using MMAS. The results showed adherence to taking medication in the intervention group before test was carried out was 1.45, while the average adherence to taking medication after test was 2.74, this indicates that there is an average difference before and after the intervention treatment in the intervention group and shows that there is a significant difference when viewed from t value 24.005 > 1.984 and P value of 0.000. It can be concluded that there is a significant effect of the telenursing program on medication adherence in pulmonary tuberculosis patients.